1986
DOI: 10.1111/j.1432-1033.1986.tb09701.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane proton ATPase from human kidney

Abstract: Distal urinary acidification is thought to be mediated by a proton ATPase (H+‐ATPase). We isolated a plasma membrane fraction from human kidney cortex and medulla which contained H+‐ATPase activity. In both the cortex and medulla the plasma membrane fraction was enriched in alkaline phosphatase, maltase, Na+,K+‐ATPase and devoid of mitochondrial and lysosomal contamination. In the presence of oligomycin (to inhibit mitochondrial ATPase) in the presence of ouabain (to inhibit Na+,K+‐ATPase) and in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Since DCCD was also a potent inhibitor of mitochondrial ATPase (21), NEM was considered more specific. The higher concentration of NEM required for OIMATPase inhibition was consistent with reports for H+-ATPases in other tissues (21)(22)(23) Colchicine, ethynylestradiol, manganese, phalloidin, and taurocholate failed to inhibit BCEF OIMATPase at concentrations up to 132 pM (Figure 1). Concentration-dependent inhibition of BCEF OIMATPase by ANIT, CD, filipin, and taurolithocholate in a low micromolar range demonstrated their direct actions on the canalicular plasma membrane (Figure 1).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Since DCCD was also a potent inhibitor of mitochondrial ATPase (21), NEM was considered more specific. The higher concentration of NEM required for OIMATPase inhibition was consistent with reports for H+-ATPases in other tissues (21)(22)(23) Colchicine, ethynylestradiol, manganese, phalloidin, and taurocholate failed to inhibit BCEF OIMATPase at concentrations up to 132 pM (Figure 1). Concentration-dependent inhibition of BCEF OIMATPase by ANIT, CD, filipin, and taurolithocholate in a low micromolar range demonstrated their direct actions on the canalicular plasma membrane (Figure 1).…”
Section: Resultssupporting
confidence: 88%
“…At 1 mM, NEM inhibited 17.4 2 4.5% (n = 4 individual preparations in duplicate) of BCEF OIMATPase. Both DCCD and NEM inhibited H+-ATPase of turtle bladder epithelium (21) and renal distal tubule of humans (22) and rats (23) associated with urinary acidification. Since DCCD was also a potent inhibitor of mitochondrial ATPase (21), NEM was considered more specific.…”
Section: Resultsmentioning
confidence: 99%
“…The disparity in the ATPase activities among the three ABO homogenates can be attributed primarily to variation in the amount of V-ATPase actually present in each homogenate (total protein was determined, so inclusion of excess foot tissue, for example, would lower the V-ATPase content) and to variation in the amount of Pi released through dissociation of endogenous ATP or other phosphorylated substrates during tissue processing and assay procedures. The activity of the ABO V-ATPase is comparable to that reported in other animals: Onken and Putzenlechner ( 1995) reported V-ATPase activities of 20 and 10 pmol Pi/ljug protein min) in filtrates from the posterior and anterior gills of Eriocheir sinensis, respectively, whereas Al-Fifi et al (1998) found a higher activity of 192.3 pmol PiAjug protein min) in a 600 X g supernatant obtained from the homogenates of Malpighian tubules in Locusta, and Sallman et al (1986) reported V-ATPase activities of 30.8 pmol PiAjug protein min) and 42.4 pmol Pi/(;ug protein min) in homogenates respectively obtained from the cortex and medulla of human kidneys.…”
Section: Tahli-isupporting
confidence: 78%